2021
DOI: 10.1186/s12888-021-03481-y
|View full text |Cite
|
Sign up to set email alerts
|

A survey of mental health literacy in Japanese high school teachers

Abstract: Background School teachers are well-positioned to recognize mental health problems in their students and to help them seek appropriate help. Therefore, teachers need to have high levels of mental health literacy (MHL). In East Asia, however, few studies have examined MHL levels in teachers. In this study, MHL levels were investigated in Japanese teachers. Methods Teachers (n = 665) from 27 Japanese high schools answered a self-administered question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 49 publications
0
5
0
2
Order By: Relevance
“…Các nghiên cứu về năng lực SKTT đã được triển khai từ trước những năm 2000 cho đến nay, tập trung chủ yếu tại Mỹ, Úc, Anh và Canada, ngoài ra Trung Quốc hay Nhật Bản cũng có nghiên cứu và công bố về năng lực SKTT, tuy nhiên số lượng còn hạn chế. Các nghiên cứu chú ý đến ba khía cạnh của năng lực SKTT là sự hiểu biết, sự kỳ thị và tìm kiếm sự hỗ trợ và trên nhiều đối tượng khác nhau như phụ nữ sau sinh, trẻ em vị thành niên, người trên 18 tuổi, nhân viên y tế, dược sĩ cộng đồng, nhân viên trong nghành giáo dục, cộng đồng dân cư [11][12][13][14][15][16][17][18]. Các vấn đề SKTT được đề cập đến trong các nghiên cứu từ trước đến nay là trầm cảm, rối loạn lo âu, tâm thần phân liệt, rối loạn tăng động giảm chú ý (ADHD), và phần nhiều công bố về trầm cảm [11].…”
Section: Kết Quảunclassified
“…Các nghiên cứu về năng lực SKTT đã được triển khai từ trước những năm 2000 cho đến nay, tập trung chủ yếu tại Mỹ, Úc, Anh và Canada, ngoài ra Trung Quốc hay Nhật Bản cũng có nghiên cứu và công bố về năng lực SKTT, tuy nhiên số lượng còn hạn chế. Các nghiên cứu chú ý đến ba khía cạnh của năng lực SKTT là sự hiểu biết, sự kỳ thị và tìm kiếm sự hỗ trợ và trên nhiều đối tượng khác nhau như phụ nữ sau sinh, trẻ em vị thành niên, người trên 18 tuổi, nhân viên y tế, dược sĩ cộng đồng, nhân viên trong nghành giáo dục, cộng đồng dân cư [11][12][13][14][15][16][17][18]. Các vấn đề SKTT được đề cập đến trong các nghiên cứu từ trước đến nay là trầm cảm, rối loạn lo âu, tâm thần phân liệt, rối loạn tăng động giảm chú ý (ADHD), và phần nhiều công bố về trầm cảm [11].…”
Section: Kết Quảunclassified
“…However, this programme identified this as a potential group in taking the lead role of the programme. Teachers are close to students and become the earliest observers of behavioural changes in school children 11 .…”
Section: Factors Contributing Towards the Success Of The Programmementioning
confidence: 99%
“…Jorm et al ( 6 ) have already discussed programs to increase knowledge and beliefs about mental disorders and how these can help to recognize, manage or prevent them. However, a systematic review of mental health literacy programs for school teachers found their knowledge and confidence of helping children with mental disorders is usually low ( 7 ).…”
Section: Introductionmentioning
confidence: 99%